"I wanted to go here": Adolescents' perspectives on school choice. Issue 1 (2nd January 2018) - Mandic, Sandra; Sandretto, Susan; Hopkins, Debbie; Wilson, Gordon; Moore, Antoni; García Bengoechea, Enrique
ABSTRACT: New Zealand legislation removing school zones radically reshaped school choice, resulting in increased school stratification from parental choice frequently driven by social factors such as ethnic makeup of the school community. This article considers school choice through the eyes of 1, 465 adolescents from 12 secondary schools in Dunedin (New Zealand). The most common reasons for school choice included: preference for a coeducational school, school's facilities, positive comments from parents/students, and friends' enrollment. Reasons for school choice differed by who was making the decision. Social factors and school programs/facilities, rather than proximity to home, influenced school choice decisions in Dunedin.